PEMODELAN DAN SIMULASI ANTRIAN PENDAFTARAN DRIVER BARU GO-JEK DI SIDOARJO - Eko, Anugrah Putra; Sona, Mohammad Niko; Saputra, Achmad Fauzi; Rolliawati, Dwi (Majalah Ilmiah UNIKOM, 2019)
Queue is a waiting line from customers who need the services of one or more services. Queuing problems are related to efficiency, where the queue will reduce the convenience of service to customers. This also happened at the Gojek Office, the queue occurred because the number of service facilities was not proportional to the rate of new drivers coming to register. The researcher became interested in making a modeling and simulation of the new driver registration queue at the Go Jek Office by using the Multi Channel - Multi Phase model. Key words: Queue, Gojek, Modeling, simulation